Formação de professores alfabetizadores em contexto de pandemia da COVID-19 - Magalhães, Jacqueline Moreira (2024)
Introduction: During the Covid-19 pandemic, schools were shut down for an undetermined period, which extended beyond initial expectations. Private schools invested in digital platforms so that tutors would be able to teach their students online. Literacy tutors then started to plan classes and develop them in online interactions with their students. For this purpose, it was necessary to invest in continuous education. Objective: to investigate the main educational challenges for literacy tutors during the Covid-19 pandemic. Materials and method: The subjects of this qualitative approach research were four literacy tutors working at a private school network in the ABC Region in the Greater São Paulo, in Brazil. The data generation took place upon semi-structured interviews. Results: Data analysis allowed the identification of challenges experienced by the interviewed tutors during the Emergency Distance Teaching model. The results corroborated to the importance of continuing education of literacy tutors, enabling a critical consideration of their practices in the confrontation of several contexts. Discussion: the education must prioritize the exchange of experiences among the lecturers in their several practice scenarios, the constitution of practice communities, the promotion of continuous studies of specific theory and practice in literacy, this ensuring a broader equity in the development of reading and writing skills in Brazilian children